Conflict of interest in online point-of-care clinical support websites. Issue 8 (3rd February 2014) - Amber, Kyle T; Dhiman, Gaurav; Goodman, Kenneth W
Abstract : Point-of-care evidence-based medicine websites allow physicians to answer clinical queries using recent evidence at the bedside. Despite significant research into the function, usability and effectiveness of these programmes, little attention has been paid to their ethical issues. As many of these sites summarise the literature and provide recommendations, we sought to assess the role of conflicts of interest in two widely used websites: UpToDate and Dynamed. We recorded all conflicts of interest for six articles detailing treatment for the following conditions: erectile dysfunction, fibromyalgia, hypogonadism, psoriasis, rheumatoid arthritis and Crohn's disease. These diseases were chosen as their medical management is either controversial, or they are treated using biological drugs which are mostly available by brand name only. Thus, we hypothesised that the role of conflict of interest would be more significant in these conditions than in an illness treated with generic medications or by strict guidelines. All articles from the UpToDate articles demonstrated a conflict of interest. At times, the editor and author would have a financial relationship with a company whose drug was mentioned within the article. This is in contrast with articles on the Dynamed website, in which no author or editor had a documented conflict. We offer recommendations regarding the role of conflict of interest disclosure in these point-of-care evidence-based medicine websites.